INTEGRATED SKILLS TEACHING: SPEAKING AND LISTENING TOGETHER - Dadaboyeva Fayyoza Khikmatulloyevna (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation: This article examines the pedagogical approach of Integrated Skills Teaching (IST), focusing on the simultaneous instruction of  speaking and listening skills  in  foreign  language  education.  The  article  discusses  practical  strategies  for implementing IST, presents a case study from a military academic lyceum, and offers recommendations for educators seeking to integrate these skills effectively.